Interactive online brain shape visualization - Anisha Keshavan; Arno Klein; Ben Cipollini (Research Ideas and Outcomes, 2017)
The open-source Mindboggle package improves the labeling and morphometry estimates of brain imaging data. At the 2015 Brainhack event, we developed a web-based, interactive, brain shape visualization of Mindboggle outputs. The application links a 3D brain visualization with boxplots that describe shape measures across a selected cortical label. The code is freely available at http://www.github.com/akeshavan/roygbiv and a demo is online at http://roygbiv.mindboggle.info.